THE IMPACT OF CLIMATE CHANGE ON THE AGRICULTURAL SECTOR IN BALI PROVINCE - Sudarma, I Made; As-syakur, Abd. Rahman (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol.12, No.1, 2018DO - 10.24843/SOCA.2018.v12.i01.p07, 2018)
Climate change is an unavoidable thing due to global warming which has a wide impact on various aspect of life. Changes of rainfall patterns, increas of the frequency of extreme climate and an increase in air and sea levels are serious impacts of climate change that will affect the agricultural sector. For Indonesia, the threat of climate change will have a serious impact on achieving sustainable development targets. For the Bali Province, climate change causes disruption of water supply for various sectors, including agriculture sector. This is indicated by the decrease of land area that was very suitable for paddy rice untill 20% as long in the period 1990-2009. Due to changes in rainfall by climate change, the current cropping pattern of rice must also be adjusted. In an effort to address climate change, can be done through the plant of low emission varieties, use of organic fertilizers, adjusting cultivation techniques through water and land management and socializing the importance of agricultural insurance for  educing farmers' risk due to climate change.